Peran Kontent Marketing dan Free Ongkir terhadap Minat Beli Konsumen pada Shopee - Nggabut, Maria Heppylaria; Enco, Fransiska M.D; Surip, Fitrya Amanda; Lian, Yohanes Pemandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In the era of rapid globalization, information and communication technology has significantly transformed how consumers interact with products and brands. E-commerce has emerged as a highly popular shopping method, offering consumers easy and unlimited access to a wide range of products from around the world, all from the comfort of their homes. This shift presents great opportunities for businesses to expand their market reach, while also intensifying competition. One strategic approach increasingly adopted in the e-commerce sector is content marketing. Shopee, one of the largest e-commerce platforms in Indonesia, has successfully implemented this strategy. By leveraging video-based content and innovative promotions, Shopee has effectively captured consumers' attention. This research aims to explore how these two elements influence consumer buying interest on the Shopee platform. Using a qualitative approach, the study reveals that content marketing plays a crucial role in driving consumer interest in products. Additionally, the free shipping policy has been shown to significantly impact consumer purchasing decisions. This offering not only enhances the attractiveness of promotions but also contributes to increased sales, providing substantial value for both consumers and businesses. In the era of rapid globalization, information and communication technology has significantly transformed how consumers interact with products and brands. E-commerce has emerged as a highly popular shopping method, offering consumers easy and unlimited access to a wide range of products from around the world, all from the comfort of their homes. This shift presents great opportunities for businesses to expand their market reach, while also intensifying competition.